2017
DOI: 10.1002/bjs.10687
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized clinical trial of percutaneous endoscopic gastrostomy versus radiologically inserted gastrostomy in children

Abstract: PEG and RIG are both safe methods of gastrostomy insertion with a low rate of major complications. Registration number: NCT01920438 ( http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…RIG is a procedure commonly performed for long-term enteral nutrition and has been shown to have a similar safety profile to PEG. [2][3][4][5][6][7][8][9] However, there is a great deal of heterogeneity in the way it is performed and the reporting of complications in literature. This study over 5 years at a tertiary center shows that the use of predominantly 18-Fr tubes, with 15 mL water into the balloon, and use of a 3-point gastropexy technique, results in a high level of technical success and a low level of complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIG is a procedure commonly performed for long-term enteral nutrition and has been shown to have a similar safety profile to PEG. [2][3][4][5][6][7][8][9] However, there is a great deal of heterogeneity in the way it is performed and the reporting of complications in literature. This study over 5 years at a tertiary center shows that the use of predominantly 18-Fr tubes, with 15 mL water into the balloon, and use of a 3-point gastropexy technique, results in a high level of technical success and a low level of complication.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Studies have shown a similar overall rate of procedural complications between PEG and RIG placement including a recently published prospective randomized controlled trial (RCT) of 214 children where the authors show no significant difference in the complication rate comparing the procedure type. 2,8,9 It should be noted that there is a great deal of heterogeneity in the way that RIG is performed between practitioners and between institutions. The use of gastropexy or not, the number of gastropexy sutures, the size of tube, the tube type (e.g., pigtail or balloon), the use of prophylactic antibiotics, and the necessity of anesthetic involvement will all yield different responses between practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Further procedures 7 patients with PEG and 2 with PBG had conversion of their gastrostomy to a gastrojejunal feeding tube. Of the remaining 98 PEG patients, 44(45%) had a change of gastrostomy tube (PEG-PEG or PEG-BG) under GA at a median 12 months [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] post-primary procedure.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…A PEG can be an option to facilitate the supply of food and medicines, and it has been used successfully in both adult and child care [2]. The insertion of a PEG is a safe method with a low rate of serious complications [3]. PEG feeding through a gastrostomy tube has also been identified as a safe way to prevent malnutrition in children with cancer [2], but there is little data about whether it is comfortable for the child and his or her parent to use a PEG, and the frequency of complications is seldom reported.…”
Section: Introductionmentioning
confidence: 99%